Comparative analysis of Lithuanian and Polish taxation system - Šalnytė, Lina; Balkytė, Giedrė (Buhalterinės apskaitos teorija ir praktika, 2013)
Comparison of tax systems may influence opinion of investors and businessmen because countries, that have more favourable tax system and where the tax burden is less, seems more attractive for investment. Business owners, shareholders and other businessmen complain of the tax burden in Lithuania. Poland is one of the countries that managed the economic crisis, in spite of the fact that tax rates are higher in this country. The planned aim of the article is to do the comparative analysis of Lithuanian and Polish tax system. In this article the analysis and comparison of Lithuania and Poland tax systems, structural and dynamic analysis of Lithuania and Poland budgets revenue, comparative analysis of the main taxes collection and their burden are presented.